A Justice and Maslahah-Based Reconstruction of Notary Removal Regulations - Anis Mashdurohatun; Rizky Amalia Solichin; Rita Purwanti; Dedi Sutomo; Wildan Syukri (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2025)
This study critically examines the weaknesses of Indonesia’s current notary removal regulations, highlighting how they fall short in realizing justice and fulfilling the broader public interest (maslahah). A close analysis of Article 13 of Law No. 2 of 2014 on the Position of Notary shows that the regulation lacks clarity and fairness, especially because the “threat of punishment” is ambiguously treated as equivalent to a final court decision. This ambiguity weakens legal certainty and places notaries in a vulnerable position when facing disciplinary actions. Employing a socio-legal approach supported by both primary and secondary data, and framed by theories of justice, legal systems, and progressive law, the study identifies substantial gaps in legal substance, structure, and culture that hinder the regulation’s ability to protect rights and ensure professional accountability. To address these shortcomings, the study proposes a reconstruction of the regulatory framework grounded in justice and maslahah, emphasizing transparency, proportionality, ethical responsibility, and the protection of societal welfare. Academically, this research offers a new integrative perspective that brings together concepts of justice and maslahah to reform administrative regulations. It also provides a conceptual critique of the inconsistencies within the notary removal mechanism while presenting a more ethically oriented model for aligning professional accountability with Indonesia’s legal ideals and Islamic legal values. This reconstruction aims to create a fairer, more coherent regulatory system that better serves both notaries and the public